2021
DOI: 10.1111/jopr.13326
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Denture Base Adaptation Fabricated Using Conventional, Subtractive, and Additive Technologies: A Volumetric Micro‐Computed Tomography Analysis

Abstract: Purpose An in vitro study to compare the adaptation of denture bases fabricated with 4 different techniques using volumetric 3‐dimentional (3D) analysis. Material and Methods Edentulous maxillary and mandibular casts were scanned, and standardized denture bases were designed using CAD design software. The same standard tessellation language (STL) data were used to produce the denture bases with 4 different fabrication methods: compression molding (CM), injection molding (IM), PMMA milling (PM), and 3D printing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
9
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 34 publications
2
9
0
2
Order By: Relevance
“…The patterns of distortion as presented by gap distance in the three groups also come in accordance with other studies that showed that the greatest distortion occurs in the mid-palatal region due to the linear rather than volumetric shrinkage that results in the pull of the material away from the cast 9,11,22,24 . This could have a clinical significance not only on denture retention, but also on longevity of the denture considering that upper denture fracture occurs most commonly in the mid-palatal region and is mainly due to poor fit 25,26 .…”
Section: Discussionsupporting
confidence: 89%
“…The patterns of distortion as presented by gap distance in the three groups also come in accordance with other studies that showed that the greatest distortion occurs in the mid-palatal region due to the linear rather than volumetric shrinkage that results in the pull of the material away from the cast 9,11,22,24 . This could have a clinical significance not only on denture retention, but also on longevity of the denture considering that upper denture fracture occurs most commonly in the mid-palatal region and is mainly due to poor fit 25,26 .…”
Section: Discussionsupporting
confidence: 89%
“…In addition, the highest volumetric gap between the denture base and cast was observed in the compression molding and 3D printing groups at the palatal region. 28 Color maps from this present study also showed the Compression Molding group had positive discrepancies at the mid-palatal and maxillary defect areas. The Cara Print 3D-Printer and Carbon 3D-Printer groups had negative discrepancies at the palatal area and maxillary defect.…”
Section: Discussionsupporting
confidence: 66%
“…The results from this study agree with Oguz et al, where they compared the intaglio surface adaptation of complete dentures fabricated with compression molding, injection molding, 3D printing, and milling techniques. 28 For the maxillary denture, injection molding produced more accurate denture base adaptation than the 3D-printing technique (The Vida; EnvisionTEC and E-Denture; EnvisionTEC) did. In addition, the highest volumetric gap between the denture base and cast was observed in the compression molding and 3D printing groups at the palatal region.…”
Section: Discussionmentioning
confidence: 95%
“…Moreover, a deformation of the printed denture may occur when demounting the partially polymerized denture from the build platform 18 . Studies have shown that 3D printed dentures have similar space from the tissue surface at the PPS area as conventionally fabricated CDs 29 …”
Section: Discussionmentioning
confidence: 99%